Does Left Atrial Appendage Closure Reduce Mortality? A Vital Status Analysis of the Randomized PROTECT AF and PREVAIL Clinical Trials - Whang, William (J Atr Fibrillation, 2018)
Compared with warfarin, left atrial appendage closure (LAAC) reduced mortality in an analysis of the PROTECTAF and PREVAIL trials. However, these data were limited by patient drop-out.We sought to estimatethe mortality benefit with LAACusing updated vital status information.In PROTECT AF and PREVAIL, 227 of 1114 randomized subjects failed to complete 5-year follow-up. Centers were manually queried for updated vital status on 76 subjects (33%).During median follow-up 5.0 years (interquartile range 3.8, 5.1), 112 of 732 LAAC subjects (15.3%) and 79 of 382 controls (20.7%) died. The hazard ratio for all-cause mortality with LAAC compared with warfarin was 0.70 (95% CI 0.53-0.94, p=0.017).Subgroup analyses suggested that subjects <75 years and those with higher CHA2DS2-VASc score, history of transient ischemic attack or stroke, and permanent AF derived particular benefit, although interaction terms were not significant.The number needed to treat(NNT) with LAAC to prevent one death over 5 years was 16 (95% CI 10-82). Despite competing mortality risks in this elderly cohort, updated vital status data from PROTECT AF and PREVAIL revealed that LAAC was associated with 30% improved survival compared with warfarin, with an NNT of 16.